An Investigation into Salmonella and Fecal Coliform Contamination of Drinking Water in Broiler Farms in Iran - Jafari, R.A.; Fazlara, A.; Govahi, M. (International Journal of Poultry Science, 2006)
In view of the effect of water quality on poultry performance, from May to July 2005, the drinking water (source water, pipe water and drinker water) from 40 broiler farms in the rural area of Ahvaz (a city in the southwestern Iran) was sampled to determine the extent of Salmonella & coliform contamination. For Salmonella isolation, 25 ml of water was cultured in 225 ml of lactose broth at 37oC. After 24 hr, the samples were at first subcultured in TT & SC broths (1:9), and then plated on both BG & SS agars. After purified on blood agar, the suspected colonies were confirmed by usual biochemical & serological tests. Coliform count was carried out as per MPN method. The positive samples were examined for fecal coliform. Coliform counts in 20 farms (50%) were over the max. acceptable level (50 CFU/ml) for poultry water. Fecal coliform was detected in the water of all farms. From the drinker water of 5 farms, Salmonella serotypes Nienstedten, Tinda, Calvinia, Oysterbeds and Sterrenbos were isolated. This is the first report of the isolated serotypes in poultry in Iran.